2022
DOI: 10.3389/fmicb.2022.811904
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profiles From Fresh Biofilms Along a Temperature Gradient on a Hydrothermal Stream at El Tatio (Chilean Andes), as a Proxy for the Interpretation of Past and Present Biomarkers Beyond Earth

Abstract: Hydrothermal systems and their deposits are primary targets in the search for fossil evidence of life beyond Earth. However, to learn how to decode fossil biomarker records in ancient hydrothermal deposits, we must first be able to interpret unambiguously modern biosignatures, their distribution patterns, and their association with physicochemical factors. Here, we investigated the molecular and isotopic profile of microbial biomarkers along a thermal gradient (from 29 to 72°C) in a hot spring (labeled Cacao) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 105 publications
0
13
0
Order By: Relevance
“…We validated the approach depicted above (Figure ) by screening several natural samples with a set of antibodies raised against ancestral resurrected proteins: one biofilm and three samples from different silica sinters from the El Tatio geyser field in Chile, one biofilm and one fumarole regolith sample from two hydrothermal areas in Iceland, one biofilm and two sediment samples from a hydrothermal field in New Zealand, one salt crust sample from a hypersaline perennial spring in the Canadian High Arctic, and one soil sample from a Mediterranean forest near Madrid (Spain; Table S1 and Figure S7). , Out of them, sample ET1 , from El Tatio geothermal field, showed positive immunodetection with anti-β-lactamase_PNCA and anti-Trx_LBCA antibodies (Figure ), the antibodies against the theoretically oldest proteins as inferred by ASR (Table ). Later, we demonstrated that analogues to peptides A and B were indeed present in the sample (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We validated the approach depicted above (Figure ) by screening several natural samples with a set of antibodies raised against ancestral resurrected proteins: one biofilm and three samples from different silica sinters from the El Tatio geyser field in Chile, one biofilm and one fumarole regolith sample from two hydrothermal areas in Iceland, one biofilm and two sediment samples from a hydrothermal field in New Zealand, one salt crust sample from a hypersaline perennial spring in the Canadian High Arctic, and one soil sample from a Mediterranean forest near Madrid (Spain; Table S1 and Figure S7). , Out of them, sample ET1 , from El Tatio geothermal field, showed positive immunodetection with anti-β-lactamase_PNCA and anti-Trx_LBCA antibodies (Figure ), the antibodies against the theoretically oldest proteins as inferred by ASR (Table ). Later, we demonstrated that analogues to peptides A and B were indeed present in the sample (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Eleven natural samples were tested in this work, corresponding to different environments (hydrothermal, arctic, and mediterranean) and different types (silica precipitates, biofilm, salt crust, sediment, and soil). Most samples have been described elsewhere, , and their main features are gathered in Table S1. Crude liquid sample extracts to be analyzed by FSMI were prepared by ultrasonication and filtered (see SI, Experimental Section).…”
Section: Methodsmentioning
confidence: 99%
“…The lipid biomarkers for Chloroflexi are not rare within hot spring environments. They have been identified at the Orakei Korako geothermal area in the TVZ (New Zealand) (Pancost et al ., 2005 ; Kaur et al , 2015 ), in Hveravellir (Iceland) (van der Meer et al , 2008 ) and at El Tatio Middle Basin springs (Megevand et al , 2022 ).…”
Section: Hot Spring Environmentsmentioning
confidence: 99%
“…Still, broad distinctions such as prokaryote versus eukaryote, bacteria versus archaea, or bacteria versus algae, for example, are easily attainable (Brocks et al , 2003 ; Meyers, 2003 ; Derrien et al , 2017 ; Sánchez-García et al , 2020b ; Summons et al , 2022 ). Thus, specific lipids and their ratios in membranes may be used as biomarkers to identify organisms (Brocks and Summons, 2003 ; Willers et al , 2015 ), to study their adaptability and responses to environmental challenges (Cook and McMaster, 2002 ; Nichols et al , 2004 ; Sturt et al ., 2004 ; de Carvalho and Caramujo, 2018 ) and to disclose metabolic traits (van der Meer et al ., 2003 ; Carrizo et al ., 2022 ; Megevand et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation